Role of Board Diversity in Achieving Firm Value through Sustainability Performance Creation - Fonnardy, Brigita Christine (Magister Akuntansi - Universitas Atma Jaya Makassar, 2024)
This study explores the role of board diversity in achieving firm value through sustainability performance. This study uses secondary data from annual reports and sustainability reports of non-financial companies listed on the Indonesia Stock Exchange during the 2019-2021 period. The purposive sampling method was used to select 41 companies as research samples. Path analysis and linear regression statistical tests were used as analytical tools. The results show that of the board diversity factors studied, only the proportion of women on the board of directors and the competence of the board of directors have a significant positive influence on corporate sustainability performance. Meanwhile, board age and the proportion of independent commissioners also have a positive but statistically insignificant effect on sustainability performance. Foreign national members on the board of directors show an insignificant negative effect. Disclosure of sustainability performance on firm value shows a positive but statistically insignificant effect. Sobel test results show that disclosure of sustainability performance does not mediate the relationship between the variables of board age, proportion of women on the board of directors, board competence, foreign national members on the board of directors, and proportion of independent commissioners with firm value. Overall, this study contributes to understanding how factors in board diversity can influence corporate sustainability performance, although not all factors show a significant influence on firm value through sustainability performance disclosure.